Development of Busy Page Media to Introduce Nutritious and Balanced Foods to Young Children - Siti Kurniasih; Lia Ricka Pratama (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
This study aims to develop learning media using busy pages as an educational tool to introduce nutritionally balanced, healthy foods to children aged 4–5 years. Early childhood is a golden period when children need appropriate stimulation to understand the basic concepts of a nutritionally balanced healthy diet. Introducing balanced nutrition from an early age is important because it can shape good eating habits, including the consumption of staple foods, side dishes, vegetables, fruits, and water as the body's main needs. The type of research used is Research and Development (R&D) with the ADDIE model, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. In the analysis stage, the needs of children and teachers for attractive learning media were identified. Next, the design and development stage produced interactive, colorful busy pages equipped with manipulative activities in accordance with the characteristics of preoperational children. The validation results from media experts and subject matter experts showed that the product was “highly dfeasible. Based on the results of child development assessments, children were able to name examples of staple foods, side dishes, vegetables, fruits, and their functions for the body, as well as arrange food on a plate with a complete balanced nutritious meal. This busy page media is an interactive, enjoyable learning medium that is appropriate for the developmental characteristics of preoperational children.